Automatic Wood Cutting Technology and Marketing Digitalization in Wood Processing Businesses in Marindal 1 Village, Patumbak District, Deli Serdang Regency - Hasibuan, Azhari; Sutiawan, Jajang (Talenta Publisher, 2023)
Marindal 1 Village is one of the villages located in Patumbak District, Deli Serdang Regency, North Sumatra Province with an area of ​​810 Ha. Administratively, Marindal 1 Village consists of 12 hamlets and has a population of about 37,000 people. A group of people who are members of the wood processing business are engaged in the business of making furniture such as making frames, windows, and doors. The equipment used in cutting and splitting wood is assembled equipment that is prone to work accidents. In addition, the COVID-19 pandemic has also had an impact on decreasing the market share of the wood processing business. Therefore, a solution is needed in the form of an automatic wood-cutting spindle machine to prevent work accidents as well as training and assistance in the digitalization process of wood processing businesses so that they are better known by the community outside Marindal 1 Village in the hope of increasing sales turnover. The method used in this service consists of 2, namely the provision of a spindle moulder machine and the socialization of assistance in making digital marketing to partners. The output of this service is in the form of publications in national journals, YouTube videos, print and electronic media, and IPR from service videos.